PENGARUH PROMOSI, KUALITAS PRODUK, KUALITAS LAYANAN, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ULANG PADA UMKM NASI AYAM ORI - Retno Nabila Maharani (2022)
This research is a quantitative research conducted to determine the effect of promotion, product quality, service quality, and price on consumer repurchase decisions. The objects in this study are all consumers of Nasi Ayam ORI and are in the Jakarta area. This study took a sample of 100 respondents selected using purposive sampling method. Data was collected by distributing questionnaires and using Partial Least Square (PLS) in the form of SmartPLS 3.0 software to analyze the data. The results of this study indicate that (1) the promotion variable has a positive and significant effect on the repurchase decision, (2) the product quality variable has a positive and significant effect on the repurchase decision, (3) the service quality variable has a positive and significant effect on the repurchase decision, and (4) the price variable has a positive and significant effect on repurchasing decisions.